Impact of the Adoption of IFRS on the Level of Errors in Financial Forecasts - BEN NEFISSA, BASMA; Jilani, Faouzi (Lembaga Penerbit Fakultas Ekonomi dan Bisns, Universitas Trisakti, 2023)
This article deals with the relationship between adopting IFRS and the quality of financial forecasts. Indeed, we analyze the impact of the transition to international accounting standards on a particular characteristic: errors in financial forecasts. Indeed, referring to French companies belonging to the CAC 40 index followed over the period 2006 -2016. After empirical analysis, we noted that the positive effect of IFRS on the quality of financial forecasts has been noticed: the transition to IFRS has led to decreased errors. Thus, through this research, we can affirm that IFRS are quality standards that favor decreased informational asymmetry, hence a better quality of financial forecasts.